2013
DOI: 10.1017/s0954422413000103
|View full text |Cite
|
Sign up to set email alerts
|

The Maillard reaction and pet food processing: effects on nutritive value and pet health

Abstract: The Maillard reaction, which can occur during heat processing of pet foods or ingredients, is known to reduce the bioavailability of essential amino acids such as lysine due to the formation of early and advanced Maillard reaction products (MRP) that are unavailable for utilisation by the body. Determination of the difference between total and reactive lysine by chemical methods provides an indication of the amount of early MRP present in foods, feeds and ingredients. Previous research reported that the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 132 publications
(200 reference statements)
3
45
0
Order By: Relevance
“…The increase in FL and CML content with increasing conditioning temperature from 65 to 90 • C indicates that a reduced conditioning temperature during the pelleting process can reduce the progression of the MR and, therefore, possibly retain nutritive value of the food. This is in line with the general idea that increasing temperatures promote the MR (Van Rooijen et al, 2013). The absence of an increase in HMF content due to conditioning temperature is in line with the results of HMF for the unprocessed ingredient mix vs. pelleted dog food, although literature indicates that the formation of HMF is also a temperature/time dependent process (Tosi et al, 2002).…”
Section: Maillard Reaction Productssupporting
confidence: 87%
See 1 more Smart Citation
“…The increase in FL and CML content with increasing conditioning temperature from 65 to 90 • C indicates that a reduced conditioning temperature during the pelleting process can reduce the progression of the MR and, therefore, possibly retain nutritive value of the food. This is in line with the general idea that increasing temperatures promote the MR (Van Rooijen et al, 2013). The absence of an increase in HMF content due to conditioning temperature is in line with the results of HMF for the unprocessed ingredient mix vs. pelleted dog food, although literature indicates that the formation of HMF is also a temperature/time dependent process (Tosi et al, 2002).…”
Section: Maillard Reaction Productssupporting
confidence: 87%
“…The RL/TL ratio of the unprocessed ingredient mix, being 0.88, suggests that mainly the processing of the ingredients used in the recipe rather than the subsequent pelleting process underlie the RL/TL ratios for pelleted dog foods. Ingredients used in pet foods show a high variation in RL/TL ratios with RL/TL ratios of ingredients of animal origin ranging from 0.64 to 0.99, and ingredients of vegetable origin from 0.56 to 0.90 (Van Rooijen et al, 2013). Proteinaceous ingredients for pet foods are often heat-processed, as well as carbohydrate sources that are often pre-treated as the conditions used during the pelleting process are not optimal for complete starch gelatinization (Svihus et al, 2005).…”
Section: Total and Reactive Lysinementioning
confidence: 99%
“…Determination of sID Lys with a free ε-amino group (i.e., reactive Lys) circumvents this inaccuracy and provides a more reliable bioavailability estimate (Stein et al, 2007). In commercial dog foods, several studies as reviewed by Van Rooijen et al (2013) have shown a large difference between reactive and total Lys content. In commercial cat foods, the standardized ileal reactive Lys content is significantly lower compared with standardized ileal total Lys content (Rutherfurd et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Lysine susceptibility is due to the presence of the additional amino group, whilst in arginine it is due to the additional guanidinium group (65) . The nature of these reactions and the wide range of compounds formed have been reviewed elsewhere (65) .…”
mentioning
confidence: 99%
“…The nature of these reactions and the wide range of compounds formed have been reviewed elsewhere (65) . It must be considered that structural changes per se (e.g.…”
mentioning
confidence: 99%